2021
DOI: 10.3389/fpsyg.2021.767616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family Cohesion and Adaptability on Academic Burnout of Chinese College Students: Serial Mediation of Peer Support and Positive Psychological Capital

Abstract: This study aimed to explore the association between the functioning of family environment (i.e., family cohesion and family adaptability) and academic burnout of Chinese college students as well as the mediating effects of the interpersonal resource (i.e., peer support) and intrapersonal resource [i.e., positive psychological capital (PsyCap)] in this relationship. A total of 1971 Chinese undergraduates were involved in an online questionnaire survey and data analysis. It was found that family cohesion and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
1
12
0
2
Order By: Relevance
“…In this study, interpersonal resources such as support from family and positive family interaction facilitated the development of personal resources like positive attributes of adolescents. Also, it echoes the findings of Yu et al ( 45 ) which revealed the positive contribution of family cohesion and adaptability to psychological capital like self-efficacy and resilience of 1,971 Chinese college students. As pointed out by Shek et al ( 44 ), while there are many studies investigating the impact of PYD attributes on adolescent developmental outcomes, there are relatively few studies examining the antecedents of PYD attributes, particularly family factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, interpersonal resources such as support from family and positive family interaction facilitated the development of personal resources like positive attributes of adolescents. Also, it echoes the findings of Yu et al ( 45 ) which revealed the positive contribution of family cohesion and adaptability to psychological capital like self-efficacy and resilience of 1,971 Chinese college students. As pointed out by Shek et al ( 44 ), while there are many studies investigating the impact of PYD attributes on adolescent developmental outcomes, there are relatively few studies examining the antecedents of PYD attributes, particularly family factors.…”
Section: Discussionsupporting
confidence: 87%
“…Research Question 2: Is family functioning related to PYD attributes? With reference to the existing findings ( 44 , 45 ), it was hypothesized that there would be a positive relationship between these two domains (Hypothesis 2).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of positive psychology, the survival and development of college students is a process of constantly facing challenges, as well as a process of growing up in adversity [30]. Tis study identifed the mediating efect of MHL between psychological distress and psychological resilience; therefore, mental health workers should take positive measures to promote college students' psychological resilience and MHL to improve the overall mental health of college students.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to family functioning, it reflects the quality of family environment and communications among family members [ 21 ]. A high level of family functioning is significant to healthy development of adolescents [ 22 , 23 , 24 ]. The notion is particularly relevant to China where the family is closely associated with the development of adolescents [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, family functioning contributes to the development of positive youth development attributes. For example, Yu et al [ 24 ] showed that family functioning positively predicted developmental assets characterized by resilience, self-efficacy, optimism, and hope of Chinese students. Moreover, family cohesion and adaptability positively contributed to psychological capital, which in turn negatively predicted academic burnout of students.…”
Section: Introductionmentioning
confidence: 99%